Role of HLA class I antigens in the development of psoriatic arthritis and its clinical presentation - Irina Aleksandrovna Troshkina; V V Badokin; I A Guseva (Научно-практическая ревматология)
Objective: to investigate the association of HLA Class I antigens with the predisposition to psoriatic arthritis (PsA) and the severity and types of articular syndrome in PsA. Subjects and methods. The investigation enrolled 99 patients (56 females and 43 males) aged 43.5+13 years with PA with a median duration of 2 (range 0.8-10) years. An oligoarthritic type was observed in 28 patients, polyarthritic, distal, and spondyloarthritic types were present in 28, 39, and 10 patients, respectively. Two patient groups were formed according to the age at onset of psoriasis: 1) 71 patients aged less than 40 years and 2) 23 patients aged over 40 years. Results. As compared with the control group, the patients with PsA were found to have a higher frequency of HLA-B13 (odds ratio [OR] 2.72; p < 0.004), HLA-В16 (OR 3.95; p < 0.0001), and HLA-B27 (OR 3.2; p < 0.003). There was an association of the types of joint injury with HLA antigens: the distal type with HLA-B13 (OR 3.38; p < 0.02) and HLA-В16 (OR 3.95; p < 0.01), the polyarthritic type with HLA-В16 (OR 5.90; p < 0.0001) and HLA-B27 (OR 3.26; p < 0.01), and the spondyloarthritic type with HLA-B27 (OR 6.32; p < 0.001). The young onset of psoriasis was associated with HLA-B13 (OR 3.29; p < 0.001). The detection rate of the B38 antigen (the subtype of HLA-B16) was higher in all X-ray stages of PsA and was 16.4% in Stages I-IIA, 25% in Stage IIB, and 40.9% in Stages III-IV versus 8.7% in the control group, the magnitude of the association being increased with the higher degree of joint destruction. Conclusion. The detailed analysis of the investigation revealed that HLA system antigens were differently involved in the development of PsA and clinical types of articular syndrome.